Between the Plums : Visions of Sugarplums, Plum Lovin', and Plum Lucky - Evanovich, Janet; Evanovich, Janet; Evanovich, Janet (New York : St. Martin's Press, 2009)
In this special edition containing three Between-the-Numbers books, Stephanie Plum confronts a strange man in her kitchen five days before Christmas; accepts with reluctance a task allocated to her by the shadowy Diesel; and gets lucky in Atlantic City with a brown-eyed stud who has stolen her heart.
Visions of sugar plums -- Plum lovin' -- Plum lucky.
First work originally published: New York : St. Martin's Press, 2002. 2nd work originally published: New York : St. Martin's Press, 2007. 3rd work originally published: New York : St. Martin's Press, 2008.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; New Jersey -- Fiction; Fiction